ANALISIS DAYA TAMPUNG BEBAN PENCEMARAN SUNGAI SIAK BAGIAN HULU - Yos Adhie Nugroho; Mubarak Mubarak; Zulkifli Zulkifli (Program Pascasarjana Universitas Riau, 2020)
This research was conducted in April 2018 and took place in the upper reaches of batang siak river, on the Sungai Tekuana, Tekuana Pendek, and Jamu Bualo. The purpose of this research is to evaluate the waters of the upstream part in Siak River according to its status and quality based on environmental quality standards, calculate the load capacity of the upstream part of the Siak River pollutants, and determine the pollutant input from the tributaries leading to the upstream body of the Siak River. Based on the results of research BOD parameters have passed the upstream capacity of the Siak river. For sampling point 2 about -1750.43 mg / sec, sampling point 5 about -4474.31 mg / sec, and tributary point 1 about -0.42355 mg / sec, while river storage data for other parameters such as COD and TSS are still good.